Adolescentes e jovens nas mãos da justiça: a experiência socioeducativa interinstitucional de São Carlos - SP (2001-2016) - Francisco, Julio Cesar (2021)
The thesis addresses the conceptions and inter-institutional practices for the operation of the initial care to adolescents accused of infraction in the city of São Carlos (SP), as well as points pedagogical and protective subsidies for the social redirection of offenders. It was intended to answer the following research problem: what are the conceptions and inter-institutional practices of the Socio-Educational System for the operation of the initial care to the adolescent involved with the infractional act, and what are their possibilities of effective rights, duties and social integration? Methodologically, the research has a bibliographic, documental, and field profile, guided by thematic content analysis, in which 2,895 judicial processes of sentenced youths between the years 2001 and 2016 were surveyed and analyzed. The bibliographical research supported the understanding of the phenomenon studied and contributed to the process of analysis of the data collected, which allowed us to know three main aspects: I. the infractional profile of those served and the profile of the professionals of the Socioeducational System; II. the relationship between the economic, cultural and symbolic capitals of public agents and the actions with young people; III. and the foundations that underlie the Socioeducational System, identified through semi-structured interviews with professionals from sectorial and institutional policies. The results of the research indicate perspectives of cooperation among the institutions for the functioning of the procedures of investigation and welcoming of youth accused of infractions, in which a control and a significant reduction of infractions over time, especially of serious infractions, is perceived. It was identified a will of the agents of the public power to congregate the responsibilities among institutions and partners from society, in order to seek a better articulation of the socio-educational work and offer a more adequate structure to the young people, guided by the technical-scientific, repressive-reproductive, and humanistic-existential educational tendencies. In the diversity of conceptions and specificities in the functions of each institution, there is an engagement for the consolidation of a pedagogy of cooperation, which gave origin and support to the unprecedented project called Núcleo de Atendimento Integrado - NAI, strengthening the local socio-educational policy. Nevertheless, the work in the initial care of young people accused of committing infractions lacks a more protective action and specialized pedagogical follow-up in the judicial sphere of childhood and youth, especially to mitigate the problems of school dropout, family abandonment, and the incidence of drug trafficking.